Salivary pH Effect on Orthodontic Appliances: In Vitro Study of the SS/DLC System - António Fróis (MDPI AG, 2021)
Stainless steels (SS) are the most-used alloys for manufacturing fixed orthodontic appliances due to their attractive set of mechanical properties, biocompatibility, and high corrosion resistance. Nevertheless, during regular orthodontic treatments–taking at least around 2 years–the intraoral environment inevitably degrades these bioalloys, releasing metallic ions into the oral cavity. In the first part of this in vitro study, the corrosion resistance of commercial SS appliances (brackets, tubes, and bands) was evaluated in Fusayama-Meyer artificial saliva at pH values of 2.3 and 6.8 over the course of 30 days. As expected, the results corroborated that salivary pH highly influences corrosion behaviour. Released Ni, Cr, and Fe were within dietary intake values. In the second part, a novel approach for oral corrosion prevention based on the chemical inertness of DLC materials is presented. SS surfaces were functionalized with biocompatible a-C:H-sputtered coatings and submitted to the same experimental conditions. The anticorrosion ability of this system was demonstrated, preventing the pitting corrosion that occurred on the SS substrates. Despite the galvanic coupling effect due to the presence of the Cr-based interlayer, this study enhanced the potential use of the reactive sputter-deposited a-C:H coatings in orthodontics.